Faith, Culture, and Technology in EFL Classrooms: Ethnographic Insights from Professional Learning Communities in Indonesian Islamic Schools - Fadlilah, Sayyidatul; Yuliasri, Issy; Fitriati, Sri Wuli (Dinamika Ilmu, 2025)
Integrating Technological Pedagogical Content Knowledge (TPACK) in English as a Foreign Language (EFL) teaching necessitates striking a balance between global educational innovations and local cultural and religious contexts. This ethnographic study examines how faith-based values and cultural norms influence the integration of TPACK among EFL teachers in the Professional Learning Communities (PLCs) of Indonesian Islamic schools. Using a multidisciplinary framework combining educational technology, sociocultural theory, and religious studies, the research addresses: (1) How do faith and culture shape teachers’ TPACK practices? (2) What challenges and opportunities arise in aligning technology with Islamic educational values? (3) How do PLCs help or hinder culturally responsive TPACK development? Data were collected through classroom observations, field notes, photo voice, and school documents. Findings indicate that religious and cultural commitments influence technology adoption and enhance lesson relevance by connecting to students' experiences. PLCs provide collaborative spaces to address value-based concerns, share strategies, and co-create approaches that ensure teaching effectiveness and cultural and religious consistency. The study highlights the need for context-sensitive professional development to facilitate the sustainable integration of technology in EFL settings.